(untitled) - Tunis, Edwin; 1897- (Cleveland, 1965)
Describes and illustrates the work of craftsmen and artisans in Colonial America. Shows types of work done in town shops and manufacturies, as well as, in homes, village shops, and country forges.
Keywords: Decorative arts, Early American; Technology; History; United States; Decorative arts, Early American; Technology; History; United States; United States; Industries; United States; To 1775; Social life and customs; United States; Industries; United States; Social life and customs; To 1775